2011
DOI: 10.1088/0741-3335/53/5/054016
|View full text |Cite
|
Sign up to set email alerts
|

Theory of fast particle generation in front of LH grills

Abstract: During tokamak operation with lower hybrid (LH) power a few per cent of the launched power is absorbed by the scrape-off layer plasma in magnetic flux tubes in front of the LH grill. At strike points of these flux tubes, intense plasmawall interaction is seen in visible and infrared wavelengths, and local wall damage can occur. The parallel power flux within these 'hot spots' is estimated to be up to about 10 MW m −2 by infrared imagery. Recent experimental results from retarding field analyzer measurements on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 16 publications
1
25
0
Order By: Relevance
“…At Tore-Supra, a similar mid-plane surface heating associated with fast ions was observed 9 , though this phenomenon is distinct from hot spots on antenna limiters associated with rectified RF sheaths 45 . Previous studies have suggested that a small fraction of LH power can generate fast electrons during the transit across the scrape-off layer (SOL) into the plasma core 17,49 .…”
Section: A Erosion and Localized Surface Heating During Ion Cyclotromentioning
confidence: 99%
See 1 more Smart Citation
“…At Tore-Supra, a similar mid-plane surface heating associated with fast ions was observed 9 , though this phenomenon is distinct from hot spots on antenna limiters associated with rectified RF sheaths 45 . Previous studies have suggested that a small fraction of LH power can generate fast electrons during the transit across the scrape-off layer (SOL) into the plasma core 17,49 .…”
Section: A Erosion and Localized Surface Heating During Ion Cyclotromentioning
confidence: 99%
“…During certain operating conditions, these actuators have been observed to cause additional PMI 9,17,18 . Imaging diagnostics have also been beneficial for investigating these phenomena.…”
Section: Introductionmentioning
confidence: 99%
“…Some simulation tools, including the antenna-plasma coupling code, 17 particle in cell (PIC) simulation code, 18 were developed in order to calculate the fast electron flux driven by LHCD. In a theoretical study, 19 fast electron generation in a wide layer of several centimeters was investigated. It has been predicted that the edge coherent structures, such as blobs which normally carried dense hot plasma, significantly enhance the current drive effect of LHCD.…”
Section: Introductionmentioning
confidence: 99%
“…It has been predicted that the edge coherent structures, such as blobs which normally carried dense hot plasma, significantly enhance the current drive effect of LHCD. 19 During both 2010 and 2012 experimental campaigns, five bright spots, corresponding to five rows on the LHCD antenna, were routinely observed by visible charge coupled device (CCD) cameras in EAST when LHCD was applied. In previous numerically and experimentally investigations, those visible belts were attributed to static helical current filaments 20,21 flowing along the magnetic field lines in SOL.…”
Section: Introductionmentioning
confidence: 99%
“…48 In those experiments there will rarely be an energetic ion population (only in cases of simultaneous ICRH input), but the FILD's ability to detect hard x-rays and its proximity to the lower hybrid launcher may prove useful in investigating new theories concerning energetic electron generation near lower hybrid grills. 49 The D α trace in Fig. 9(c) is shown to demonstrate that the FILD signals do not correlate with edge light outside of disruptions.…”
Section: Analysis and Initial Resultsmentioning
confidence: 93%